METHODOLOGY FOR ENSURING INTERDISCIPLINARY CONNECTIONS IN TEACHING UZBEK MUSIC HISTORY TO STUDENTS - Nurullayev Farrukh Gaybulloyevich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This study examines methodological approaches to ensuring interdisciplinary integration in teaching Uzbek Music History to students in higher music education. Contemporary music pedagogy increasingly recognizes that historical musical knowledge cannot be effectively taught in isolation from related disciplines such as ethnomusicology, literature, history, philosophy, linguistics, and cultural studies. In the Uzbek context, musical traditions such as maqom, folk genres, and twentieth-century professional composition are deeply intertwined with poetic texts, social institutions, religious thought, and historical processes. The article analyzes how interdisciplinary connections can be systematically incorporated into curriculum design, teaching strategies, and assessment practices. Drawing on international educational theory and music pedagogy research, the paper argues that interdisciplinary teaching enhances students’ analytical thinking, cultural awareness, and professional competence.